Agomelatine Prevents Amyloid Plaque Deposition, Tau Phosphorylation, and Neuroinflammation in APP/PS1 Mice - Yang, Xiao-bo; Zu, Heng-bing; Zhao, Yong-fei; Yao, Kai (Frontiers in Aging Neuroscience, 2022)
Agomelatine, an agonist of melatonergic MT1 and MT2 receptors and a selective 5-hydroxytryptamine 2C receptor antagonist, is widely applied in treating depression and insomnia symptoms in several neurogenerative diseases. However, the neuroprotective effect of agomelatine in Alzheimer's disease (AD) is little known. In this study, a total of 36 mice were randomly divided into three groups, including the group of wild-type (WT), APP/PS1 and agomelatine (50 mg/kg). After 30 days, the Morris Water Maze was performed to test the cognitive ability of mice. Then all mice were sacrificed, and the hippocampus tissues were collected for ELISA, western blot and immunofluorescence analysis. Here, we found that agomelatine attenuated spatial memory deficit, amyloid β (Aβ) deposition, tau phosphorylation and neuroinflammation in the hippocampus of APP/PS1 mice. Further study demonstrated that agomelatine treatment up-regulated the protein expression of DHCR24 and down-regulated P-Akt, P-mTOR, p-p70s6k, HES1 and NOTCH1 expression. In summary, our results identified that agomelatine could improve cognitive impairment and ameliorate AD-like pathology in APP/PS1 mice via activating DHCR24 signaling and inhibiting Akt/mTOR and HES1/NOTCH1 signaling pathway. Agomelatine may become a promising drug candidate in the therapy of AD.